PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) DALAM MENINGKATKAN KEAKTIFAN PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS III SDN 186/I SRIDADI - Aziza Maharani; Barokah, Tetty; Sari, Maya; Putri, Nadia; Risdalina, Risdalina; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve student learning activeness through the implementation of the cooperative learning model Team Games Tournament (TGT) in the subject of Natural and Social Sciences (IPAS) for Grade III students at SDN 186/I Sridadi. The research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 16 third-grade students. Data collection techniques included observation, interviews, and documentation. The results showed that the implementation of the TGT model significantly increased student learning activeness. In Cycle I, student activeness was categorized as